Paradoxical increase of neurofilaments in SMA patients treated with onasemnogene abeparvovec-xioi - Flotats-Bastardas, Marina; Bitzan, Lisa; Grell, Charlotte; Martakis, Kyriakos; Winter, Benedikt; Zemlin, Michael; Wurster, Claudia D.; Uzelac, Zeljko; Weiß, Claudia; Hahn, Andreas (Frontiers in Neurology, 2023)
Background/Objective: Neurofilament light chain (NfL) has been proposed as a biomarker reflecting disease severity and therapy response in children with spinal muscular atrophy type 1 and 2 (SMA1 and 2). The objective of this study was to examine how serum NfL changes after gene replacement therapy (GRT) with onasemnogene abeparvovec-xioi. Methods: We measured NfL in serum probes from 19 patients (10 SMA 1 and 6 SMA 2; 15 previously treated with nusinersen or risdiplam; 12 male) before and at variable time points after GRT. These values were related to motor scores (CHOP-Intend, HFMSE and RULM). Results: Median age at GRT was 19 months (range 2-46 months). Median NfL of all patients before GRT was 39 pg/ml (range 0-663 pg/ml; normal values <25 pg/ml), increased significantly to 297 pg/ml (range 61-1696 pg/ml; p<0,002) 1 month after GRT, and decreased to 49 pg/ml (range 24-151 pg/ml) after 6 months. Subjects pre-treated with nusinersen or risdiplam had lower baseline NfL levels than naïve patients (p<0,005), but absolute increases of NfL were similar in both groups. While motor scores were improved in 14 out of 18 SMA patients (78%) 6 months after GRT NfL values differed not significantly from those measured at baseline (p=0,959). Conclusion: Serum NfL showed a paradoxical transient increase after GRT in both, pre-treated and naïve patients, which may reflect an immunological reaction in the CNS related to transfection of neuronal cells by AAV9. The clinical meaning of this increase should be assessed in future studies. Our findings encourage regular monitoring of NfL in OA treated patients.